[Retracted Article] Mapping Research Trends of TikTok in Education: A Bibliometric Analysis - Siti Nurjanah; Shaufi Ramadhani; Zafrullah Zafrullah; D’aquinaldo Stefanus Fani Seran; Rooskartiko Bagas Rahoetomo; Sandry Rory (Universitas Sebelas Maret, 2024)
NOTICE OF ARTICLE RETRACTION Dear Readers and Stakeholders,We hereby announce that the article titled